Systemic inflammatory markers as independent prognosticators of head and neck squamous cell carcinoma. Issue 1 (15th April 2014) - Rassouli, Alipasha; Saliba, Joe; Castano, Roberto; Hier, Michael; Zeitouni, Anthony G.
Abstract Background The purpose of this study was to investigate the prognostic value of the pretreatment inflammatory markers platelet‐to‐lymphocyte ratio (PLR) and the neutrophil‐to‐lymphocyte ratio (NLR) in patients with head and neck squamous cell carcinoma (HNSCC). Methods We conducted a retrospective analysis of patients diagnosed with HNSCC at McGill University Health Center from 2000 to 2011 (273 patients were retained). Hematologic parameters were recorded within 4 weeks of diagnosis. Mortality and recurrence rates were compared according to various PLR and NLR thresholds. Results Of the total patients, 20.5% died and 11.0% had disease recurrence. PLR >170 was associated with higher mortality (p = .008). The subgroup with a combination of PLR >170 and NLR ≤3.0 was associated with higher T classification and highest mortality (43%). NLR above 4.2 predicted higher rates of recurrence (p < .0001). The NLR/PLR combination was at least as good as TNM staging in predicting survival. Conclusion PLR is an independent predictor of mortality; NLR is an independent predictor of recurrence in HNSCC. These parameters might be used to identify advanced stages rapidly and economically. © 2014 Wiley Periodicals, Inc. Head Neck37: 103–110, 2015